Transformation of Butterfly Pea (Clitoria ternatea) F3'5'H (Flavonoid-3',5'-Hydroxylase) Gene into Patumma (Curcuma alismatifolia) ‘Blue Moon’ - Thamaragsa, Nitchamon; Chundet, Ruttaporn; U-Kong, Warut (Thai Journal of Science and Technology, 2021)
Patumma (Curcuma alismatifolia) is a Zingiberaceae family with beautiful colors and needs to the market. There is one of the flower bulbs that make a high income. Patumma bulb was exported to foreign countries. When compared with the types of cut flowers and popularity, the improvement on a new appearance, value-added and competitive of Patumma, was necessary. In this research, the progress of Patumma ‘Blue Moon’ to blue shade was studied. The isolation, cloning, and characterization of flavonoid-3',5'-hydroxylase (F3'5'H) genes of butterfly pea (Clitoria ternatea), encoding an enzyme involved in the coloration of plant blue pigment, was the focus. The F3'5'H gene was isolated from butterfly pea (Clitoria ternatea and transferred to retarded shoot of Patumma ‘Blue Moon’ using Agrobacterium-mediated transformation technique. The results show that the F3'5'H genes were inserted into Patumma genome and expressed in the transcription phase. The study on Patumma ‘Blue Moon’ coloration found that transformed Patumma is bluer than non-transformed Patumma ‘Blue Moon’, but purple. All obtained results can be concluded that we successfully transformed Clitoria ternatea F3'5'H gene into Patumma and these genes could be expressed and changed the color of Patumma. Based on the findings, the knowledge to improve the color of flowers using genetic engineering is possible to be applied to improve other flowering plants to increase value and opportunity in the market.